2023
DOI: 10.1038/s41598-023-31258-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term concentration of tropical forest nutrient hotspots is generated by a central-place apex predator

Abstract: Apex predators typically affect the distribution of key soil and vegetation nutrients through the heterogeneous deposition of prey carcasses and excreta, leading to a nutrient concentration in a hotspot. The exact role of central-place foragers, such as tropical raptors, in nutrient deposition and cycling, is not yet known. We investigated whether harpy eagles (Harpia harpyja) in Amazonian Forests—a typically low soil fertility ecosystem—affect soil nutrient profiles and the phytochemistry around their nest-tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Manipulative experiments or remotely sensed trail cameras can be used to evaluate food web‐related effects that occur in and around patches (Cortés‐Avizanda et al 2009a, Ruprecht et al 2021, Spencer et al 2021, Zhao et al 2022). Similarly, remote cameras can be used to estimate rates of nutrient accumulation by recording the rate, type, and quantity of prey remains brought to and concentrated at specific locations (de Miranda et al 2023).…”
Section: Quantifying Patchy Indirect Effects Of Predation At Local An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Manipulative experiments or remotely sensed trail cameras can be used to evaluate food web‐related effects that occur in and around patches (Cortés‐Avizanda et al 2009a, Ruprecht et al 2021, Spencer et al 2021, Zhao et al 2022). Similarly, remote cameras can be used to estimate rates of nutrient accumulation by recording the rate, type, and quantity of prey remains brought to and concentrated at specific locations (de Miranda et al 2023).…”
Section: Quantifying Patchy Indirect Effects Of Predation At Local An...mentioning
confidence: 99%
“…calcium, nitrogen, phosphorous) (Schmitz et al 2010, Monk and Schmitz 2022). When predators transport these limiting nutrients into concentrated locations, they can create biogeochemical hotspots on the landscape (Gharajehdaghipour et al 2016, de Miranda et al 2023). Notably, these predator‐mediated nutrient patches occur separate from whether or not predators alter the density or traits of prey.…”
Section: Introductionmentioning
confidence: 99%
“…The parental care section also needs updating: it inaccurately states that young nestlings are fed twice a week. Miranda et al (2023) found that male Harpy Eagles deliver prey every 1.8 days during the initial weeks post-hatching. Concerning the post-fledging independence period, while eaglets may begin hunting at 12 months, they remain dependent on their parents for a much longer period than what the authors state, generally one to two additional years, with larger female eaglets having longer dependency intervals (Miranda et al 2023).…”
mentioning
confidence: 99%
“…Miranda et al (2023) found that male Harpy Eagles deliver prey every 1.8 days during the initial weeks post-hatching. Concerning the post-fledging independence period, while eaglets may begin hunting at 12 months, they remain dependent on their parents for a much longer period than what the authors state, generally one to two additional years, with larger female eaglets having longer dependency intervals (Miranda et al 2023). We are recommending only minor revisions to this species account, some of which include data not available at the time of the guidebook's publication.…”
mentioning
confidence: 99%